2014
DOI: 10.1117/12.2062767
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated nanoparticles: protein corona and secondary structure

Abstract: Nanoparticles have important biological and biomedical applications ranging from drug and gene delivery to biosensing. In the presence of extracellular proteins, a "corona" of proteins adsorbs on the surface of the nanoparticles, altering their interaction with cells, including immune cells. Nanoparticles are often functionalized with polyethylene glycol (PEG) to reduce this non-specific adsorption of proteins. To understand the change in protein corona that occurs following PEGylation, we first quantified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…The subsequent interaction of the immune system with NPs is mediated by a layer of blood serum proteins that adsorb on the NP surface during circulation. This opsonization, resulting in a ''corona'' of proteins on the NP surface (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), can be decreased by PEGylation, but complete inhibition remains a challenge (16)(17)(18)(19)(20)(21)(22). The protein corona, described as either a ''hard'' corona of tightly bound proteins or a ''soft'' corona of dynamic, weakly bound proteins (23)(24)(25)(26), has been studied extensively as a function of NP diameter, composition, and surface functionalization (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent interaction of the immune system with NPs is mediated by a layer of blood serum proteins that adsorb on the NP surface during circulation. This opsonization, resulting in a ''corona'' of proteins on the NP surface (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), can be decreased by PEGylation, but complete inhibition remains a challenge (16)(17)(18)(19)(20)(21)(22). The protein corona, described as either a ''hard'' corona of tightly bound proteins or a ''soft'' corona of dynamic, weakly bound proteins (23)(24)(25)(26), has been studied extensively as a function of NP diameter, composition, and surface functionalization (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…711 For example, PC composition can promote or deter the interaction of NPs with outer membrane receptors for specific cell uptake, 12, 13 or impact their blood circulation lifetime. 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Here, not only amount of adsorbed protein, but also type and configuration of them must be considered since they determine the fate of nanoparticles by opsonization 10,12,13 . To attain longer half-life for nano scale delivery systems, the most prevalent strategy is to cover the surface of nanoparticles by some polymers such as polyethylene glycol (PEG) [14][15][16] , poloxamer 17 , and dextran 18,19 . Gref et al fabricated a series of PEG-coated poly lactic acid (PLA), poly (lactic-co-glycolic acid) (PLGA) and poly ε-caprolactone (PCL) nanoparticles with different molecular weights (Mw) of PEG, and showed that adsorption of plasma proteins to the nanoparticles depends on PEG size and content 20 .…”
mentioning
confidence: 99%